Nigeria And Conflict Resolution in Mali: A Focus on Specific Contributions - Idagu, Adie Edward; Obiageli, Nwokedi Lawretta; Luka, Mahwash Benedict (International Journal of Conflict Management, 2020)
Purpose: This study focuses on the conflict in Mali and the specific contributions of Nigeria towards its resolution. It draws its data from the secondary sources such as textbooks, journals, articles, and the likes from the University of Abuja library, Abuja, the researchers' libraries as well as the internet. Methodology: The study employs a qualitative method based on content analysis in analyzing the data collected. Also, the study adopts the theory of realism as a framework to provide explanation for Nigeria's engagement in the conflict. Results: From the findings, it is cleared that Nigeria contributed significantly to the resolution of the Malian impasse, being the leader of the continent where Mali is located and having a clear foreign policy principle that promotes Africa centeredness. And more importantly, as a way to ensure her own survival since the dreaded Boko Haram set was reported to have established link with the terrorist group in Mali. Unique contribution to theory, policy and practice: Thus, some of these contributions were statement of condemnation, cash donation, personnel contribution and the initiation of peacekeeping mission among others. Some recommendations have also been made in the paper. Accordingly, Countries within the sub-region of West Africa should cooperate with and support Nigeria when necessary to chart a new course that will guarantee durable peace and stability in Mali; The Malian government and the rebel groups should always embrace dialogue as a way out of their conflict rather than resorting to violence; The Malian authority on its own acknowledged Nigeria's crucial contribution towards the stability of Mali. This should be commended as the gesture will go a long way towards encouraging Nigeria to do more for others.